Clinicians' attitudes towards patient involvement in mental health research. Issue 1 (January 2016) - Carmichael, Juliet; Misselbrook, Thomas; Marriner, Leah; Forrest, Alexandra; Molodynski, Andrew
Abstract : Mental health studies often recruit a low number of participants and Welcome Trust data have shown that less than a third of the trials successfully achieved their recruitment targets within the time frame given. The authors at the Oxford Health NHS Foundation Trust surveyed community staff to analyse the barriers to mental health research studies but also to uncover strategies for the future, which have the potential to shift the balance towards better patient recruitment into research and ultimately to secure future care informed by robust evidence.